Structure–activity relationship study of secondary metabolites from Mesua beccariana, Mesua ferrea and Mesua congestiflora for anti-cholinesterase activity - Teh, Soek Sin; Cheng, Gwendoline Lian Ee; Mah, Siau Hui; Ahmad, Zuraini (Springer Verlag, 2016)
Our search for potential anti-acetylcholinesterase (AChE) inhibitors for treatment of Alzheimer’s disease has led to the discovery of two bioactive compounds, α-mangostin (11) and congestiflorone acetate (13). This discovery was achieved from a preliminary screening of the anti-AChE activity on the extracts of three Mesua species namely M. ferrea, M. beccariana and M. congestiflora using Ellman’s method. The pure metabolites, 1–12 which were isolated from the Mesua species, along with a synthetic derivative, compound 13 were then evaluated for their activities in order to identify the compounds that correspond to the enzyme inhibitory activities. Compounds 11 and 13 were found to give significant anti-AChE activities with IC50 values of 17.51 and 20.25 µM.